Post-Stroke Depression and Activities of Daily Living: Sex-Differentiated Analysis of the Moderating Role of Physical Activity in Older European Adults - De Moraes-Ferrari, G (SAGE PUBLICATIONS INC, 2026)
Objectives To examine the mediating role of activities of daily living (ADL) in the association between stroke and depressive symptoms, and to investigate whether moderate physical activity (MPA) moderates this mediation in older adults, using sex-stratified analyses. Methods Cross-sectional data from 31,137 participants (>= 65 years) were analysed using wave eight of the Survey of Health, Ageing and Retirement in Europe. Depression, ADL limitations, stroke history and weekly frequency of MPA were assessed. Mediation and moderated mediation analyses were conducted. Results ADL partially mediated the association between stroke and depression in males (36.53%) and females (37.20%). In males, both medium and high weekly frequencies of MPA significantly moderated the direct and indirect associations between stroke, ADL and depression. In females, only a high frequency of MPA (> once per week) showed a significant moderating effect. Conclusion Limitations in ADLs represent an important pathway linking stroke and depression in older age.